Cidades Inteligentes: as opiniões dos usuários do SUS sobre os serviços e as ferramentas online em duas Unidades Básicas de Saúde de Vitória-ES - Borel, Flavia Miranda Sarmento (2022)
Introduction: when thinking about smart cities the association with digital technologies is inevitable. It is also noticed that the most important actor in cities – population – is usually ignored when one intends to transform them into intelligent ones. Within this theme, areas such as innovation, digital cities, information and communication technology (ICT) and users participation are very relevant points. Its relevance is understood for the discussion and understanding of how some cities in Brazil and in the world are dealing with the changes in their spaces in search of this new concept of urban spaces. The city of Vitória, capital of Espírito Santo, is also one of those cities that have implemented in some areas, such as health, tools and services considered intelligent. Objective: the research proposed to verify the opinions of users who use the Health Unic System (SUH) in that city, in two Basic Health Units (UBH), about the services and smart tools implemented in the SUH. Method: to respond to the research objectives, questionnaires were applied to users who use the SUH in the Basic Health Unit of Ilha de Santa Maria and in the Basic Health Unit of Santo André and semi structured interviews with servers and health advisors linked to the these UBH's. The work was guided by a quantitative and qualitative approache. With the information in hand, the data were analyzed using descriptive statistics, comparison and content analysis. Conclusion: it was found that the new format of offering technological services and tools, considered intelligent, provided many positive opinions, common to the users of the two UBH's, such as improving the services offered and the quality of life. However, there are points that need attention, such as the fact that technology has not solved basic problems, such as the poor quality of the internet and the difficulty in making appointments through the application, the lack of preparation, both of users and servers, for new services and technologies, in addition to being units that serve people with different profiles and social realities.